TECHNOLOGY ADAPTATION STRATEGY IN ISLAMIC BOARDING SCHOOL QUALITY MANAGEMENT: SYSTEMATIC LITERATURE REVIEW AND META ANALYSIS - Sudirman; Naf'an Tarihoran; Enung Nugraha (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Islamic boarding schools as the oldest Islamic educational institutions in Indonesia are faced with the challenge of maintaining their relevance amidst increasingly massive digitalization. This research aims to identify and analyze effective technology adaptation strategies in improving Islamic boarding school quality management. The method used was a systematic literature review (SLR) and meta-analysis using the PRISMA protocol, resulting in 8 high-quality articles that met the inclusion criteria from a total of 578 articles identified. The research results show that technology adaptation strategies have a significant positive influence on Islamic boarding school quality management with a combined effect size of 0.65 (medium-strong category), with the strongest influence on financial management (d=0.83) and administrative efficiency (d=0.78). The three main patterns of technology implementation in Islamic boarding schools identified are the gradual digital transformation model, the selective adaptation model, and the comprehensive digital transformation model, with implementation success rates between 68-75%. This research recommends a gradual approach in implementing technology by considering the unique characteristics of Islamic boarding schools, developing human resource capacity through continuous digital literacy training, and establishing strategic collaborations with the government and private sector to overcome technological infrastructure limitations..